An analysis of the impact of product recall on stock prices based on Google trend search counts - Ahyun Kim; Sang Gun Lee; Donghyuk Shin (Global Business & Finance Review (GBFR), 2020)
Purpose: Recall can have a critical impact on a companys image and reputation, and is one of the biggest issues for customers. In this study, we take the Event Study approach to analyze the impact of recall on corporate stock prices. In previous works, conflicting conclusions were drawn depending on the recall case and data collection process. Design/methodology/approach: To alleviate such issues, we utilize data as a more objective Google Trends. Specifically, we study the effects of product recall on stock prices from multiple aspects including (1) Google Trend search volume, (2) type of recall, (3) industry category, and (4) by country. Findings: Though we find that recall does not have a statistically significant effect on company share prices, we identified that recalls of companies with high search volume has a greater impact than those with low search volume. We also find that involuntary recalls have a greater impact than voluntary recalls, and non-automobile industries have a greater impact than the automobile industry. Research limitations/implications: The limitation of the research is that Google cannot accurately represent the world. It may not be fully reflected because there are countries that cannot use Google due to lack of IT infrastructure or government regulations. Also, it is not possible to know exactly when the information will leak when an event occurs. This is because if information had already leaked through peoples oral traditions before it spread to the news, its influence would be reduced. Originality/value: For studies using traditional event studies, the choice of events was very likely to be chosen according to the choice of researchers. This study is significant in that it tried to solve this problem with Google Trends and investigated all the data mentioned on the Internet except for countries that could not access Google due to lack of government regulations or IT infrastructure.
Keywords: 650; Google trend; Product recall; Event study; Automobile; Non-Automobile